Matching method harvesting and transport operations in the process of operational planning - Сидорчук, Олександр Васильович; Дуганець, Віктор Іванович; Комарнiцький, Сергій Петрович; Днесь, Віктор Ігорович; Сидорчук, Леонід Леонідович (Eastern-European Journal of Enterprise Technologies, 2012)
Developed a method for matching harvesting and transport operations in their operational planning, taking into account the stochasticity of agrometeorological and substantive components of the project environment